Liliana Suárez Navaz y Rosalva Aida Hernández (eds.): Descolonizando el Feminismo: Teorías y Prácticas desde los Márgenes. Ediciones Cátedra, Madrid, 2008 - Madonia, Salvatore (Foro Interno, 2009)
Sin resumen